Isolation and characterization of antibacterial actinomycetes from BRIS soil in Setiu, Terengganu, targeting ESKAPE infections - Amirah Ahmad; Hamidah Idris; Mohd Fakharul Zaman Raja Yahya (Penerbit Universiti Kebangsaan Malaysia, 2025)
Antibiotic resistance poses a significant challenge to global health, necessitating the discovery of novel antimicrobial agents. Actinomycetes are prolific producers of bioactive compounds, contributing to over two-thirds of clinically utilized antibiotics. While actinomycetes are widely recognized for their antibiotic production, little is known about those from BRIS soil in Setiu, Terengganu, and their antibacterial efficacy against ESKAPE pathogens remains unexplored. This study evaluated the antibacterial activity of actinomycetes isolated from BRIS soil in Setiu, Terengganu, specifically against ESKAPE pathogens. The isolates were characterized by color groups, extracted using ethyl acetate and methanol, and screened for antibacterial activity using a gel plug assay. A selected actinomycete isolate was further analyzed by gas chromatography-mass spectrometry (GC-MS), well diffusion (WD), minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) assays, along with molecular identification. The results showed that isolate BA71 exhibited the largest inhibition zones with both methanol and ethyl acetate extracts compared to the other isolates tested. GC-MS analysis of the ethyl acetate extract from isolate BA71 identified nine bioactive compounds, including stigmasta-5,24(28)-dien-3-ol, gamma sitosterol, and lupeol. The WD, MIC, and MBC assays further confirmed the isolate's bactericidal and bacteriostatic properties. Phylogenetic analysis based on 16S rRNA gene sequences revealed a close relationship between isolate BA71 and Streptomyces malaysiense MUSC 136T, with 100% similarity. These findings highlight the potential of BRIS soil-derived Streptomyces in the discovery of novel antibiotics, contributing to the ongoing search for effective treatments against ESKAPE pathogens.